Optimizing fundamental skills: fixed versus variable target approaches for volleyball serve accuracy in primary physical education - Permata, Rizky; Rizal, Rony Mohamad; Rohendi, Aep (Jurnal Ilmu Keolahragaan, 2026)
Background. Motor skill acquisition in primary physical education requires systematic manipulation of practice variables. While consistency-based learning (fixed target) and variability-based learning (variable target) represent contrasting theoretical frameworks, their differential effects on fundamental volleyball skills remain underexplored in elementary contexts. Objectives. This study compared the effectiveness of fixed target practice (FTP) versus variable target practice (VTP) on underhand serve accuracy among fifth-grade students, controlling for baseline performance differences. Methods. A quasi-experimental pretest-posttest control group design was conducted with 30 fifth-grade students (aged 10.4 ± 0.5 years; 16 boys, 14 girls) from SDN Wanaraja. Participants were assigned to FTP (n=15) or VTP (n=15) groups based on intact classes. Both groups completed 16 sessions (4 weeks, 4×/week, 45 min/session). Serve accuracy was measured using a standardized 10-trial underhand serve test. Analysis of Covariance (ANCOVA) controlled for pretest scores, while paired-samples t-tests assessed within-group changes. Effect sizes (Cohen's d, partial η²) and inter-rater reliability (Cohen's κ) were calculated. Results. ANCOVA revealed a significant main effect of practice condition on posttest accuracy, F(1, 27) = 4.53, p = .042, partial η² = .144, with FTP outperforming VTP (adjusted M = 15.08 vs. 14.41). Both groups demonstrated significant improvement (FTP: t(14) = 9.26, p < .001, d = 1.72; VTP: t(14) = 8.37, p < .001, d = 1.56). Inter-rater reliability was excellent (κ = .91). Conclusion. Fixed target practice yielded superior short-term accuracy gains; however, both approaches produced large effect sizes. A progressive pedagogical model initiating with FTP followed by VTP is recommended for elementary volleyball instruction.